Quality Status and Ecological Risk Assessment of Xixi Wetland’s Sediments - Shen, Xiu-Ying; Xue, Song; Xu, Hui-Ying; Tong, Guo-Zhang (Asian Journal of Chemistry, 2014)
The soil characteristics and content of heavy metal and persistent organic pollutants in Hangzhou Xixi wetland's sediments were tested and researched and the ecological risk of wetland's sediments was assessed by using index of single factor and HaKanson index method. The results showed that average content of sediments' heavy metal was lower than the secondary standard of Soil Environment Quality Standard (GB15618-1995). Taking Zhejiang province soil background values for risk assessment, the pollution degree of each monitoring point was medium ecological harm. The possible heavy metal source of sediments was discussed and the corresponding protective measures were putting forward.